Effect of equipment layout on bioaerosol temporal-spatial distribution and deposition in one BSL-3 laboratory. (15th August 2020) - Liu, Zhijian; Zhuang, Wenbin; Hu, Xiaoqi; Zhao, Zhiheng; Rong, Rui; Ding, Wenjun; Li, Jinsong; Li, Na
Abstract: Reasonable equipment layout is essential for creating a healthy and safe environment, especially in a three-level biosafety laboratory with high potential risk factors of infection. Since 2019, COVID-19, an emerging infection has swept the world and caused severe losses. Biosafety laboratories are mandatory sites for detecting high-risk viruses, so related research is urgently needed to prevent further laboratory-acquired infections of operators. This study investigated the effects of obstacles on exposure infection of staff in a biosafety laboratory with related experimental equipment. The numerical simulation results are highly verified by the measured results. The results indicate that although the equipment layout does not affect the bioaerosol removal time, nearly 17% of the pollutant particles in the actual laboratory cannot be discharged effectively compared with the ideal situation. These particles lingered in the lower space under the influence of vortex, which would increase the respiratory risk of operators. In addition, after the experiment a large part of bioaerosol particles would be captured by equipment and floor, and the deposition rate per unit area is 0.45%/m 2 and 0.8%/m 2, respectively. Although the results show that the equipment layout could reduce the pollution on the floor, the disinfection is still an important link, especially on the surfaces of equipment. Meanwhile, the result also indicates that the action should be light and slow when operating in BSL-3 laboratory, so as to avoid the secondary suspension pollution of bioaerosol particles on the equipment surface and floor. Highlights: Effect of equipment layout on the removal of bioaerosols in a BSL-3 laboratory was quantitatively examined. Migration rule of high-risk regions under the effect of equipment layout in a BSL-3 laboratory was explored. Comparative analysis of the polluted surfaces and sedimentary trends in two cases was conducted. Layout optimization and operation guidelines of biosafety laboratory were proposed.